Core/shell nanomaterials in photovoltaics - Elif Arici; Dieter Meissner; F. Schäffler; N. Serdar Sariciftci (International Journal of Photoenergy)
Hybrid materials consist of inorganic nanoparticles embedded in polymer matrices. An advantage of these materials is to combine the unique properties of one or more kinds of inorganic nanoparticles with the film forming properties of polymers. Most of the polymers can be processed from solution at room temperature enabling the manufacturing of large area, flexible and light weight devices. To exploit the full potential for the technological applications of the nanocrystalline materials, it is very important to endow them with good processing attributes. The surface of the inorganic cluster can be modified during the synthesis by organic surfactants. The surfactant can alter the dispersion characteristic of the particles by initiating attractive forces with the polymer chains, in which the particles should be homogenously arranged. In this review, we present wet chemical methods for the synthesis of nanoparticles, which have been used as photovoltaic materials in polymer blends. The photovoltaic performance of various inorganic/organic hybrid solar cells, prepared via spin-coating will be the focus of this contribution.